Pippi in the South Seas - Lindgren, Astrid 1907-; Bothmer, Gerry; Glanzman, Louis S. 1922-. (New York Puffin Books, 1997)
The adventures of the strongest girl in the world, who takes her two friends with her when she travels from Sweden to visit her father, king of an island in the South Seas.
Keywords: Humorous stories; Fantasy